Intellectual Structure of Knowledge in Collaborative Information Behavior: A Co-Word Analysis - Nilofar Barahmand (International Journal of Information Science and Management, 2025)
Considering the increasing importance and gradual development of research on collaborative information behavior (CIB), this study aims to investigate the current intellectual structure of knowledge on this topic, providing researchers with a basis for its future direction and development. Hence, co-word analysis was conducted on documents from Web of Science and Scopus. The network structure of the most frequent keywords was visualized using VOSviewer software. A hierarchical clustering algorithm was used to form the square matrix comprising frequently repeated keywords. To do so, SPSS software, Ward’s method, and Squared Euclidean distance method were employed, and clusters and co-word dendrogram of keywords were drawn. Furthermore, network characteristics of the co-word matrix, including centrality and density, were analyzed using UCINET software. Accordingly, quadrant and coefficient matrices were created for each cluster, centrality and density were calculated, and a strategic diagram was eventually drawn. The study comprised 316 documents published between 1992 and 2023. The most frequent keyword was "Collaborative information," and the most common co-word pair was "Collaborative Information**Information Use." Nine clusters emerged, encompassing topics such as computer-supported cooperative work, collaborative searching, system design, professional contexts, social Q&A, and collaborative learning. However, these clusters were largely undeveloped, marginal, and immature, reflecting the field's relative youth, unstable terminology, and secondary treatment in research. The findings underscore the need for further research on CIB as a central topic of the study to deepen our understanding of its diverse aspects.